Anti-Inflammatory Activity Test of N-Hexane Fraction Cream (Rhaphidophora Pinnata (L.F) Schott.) on Carrageenan Induced Back Edema in Mice - M, Hasyimi Walidah; Anayanti, Arianto; Y, Yuandani (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: One of the medicinal plants used traditionally by Indonesians is Rhaphidophora pinnata (L.f.) Schott, Family Araceae. Based on hereditary experience, the use of herbal plants is considered quite effective in treating various diseases. The results of phytochemical screening showed that Rhaphidophora pinnata leaf extract contained triterpenoid/steroid compounds which were thought to be anti-inflammatory agents. Topical administration of drugs can increase bioavailability and drug efficacy by avoiding first-pass metabolism in the liver. The advantage of the desired local effect can also be achieved with the use of topical anti-inflammatory drugs. Methods: The leaves were dried into simplicia and then the simplicia characterization was examined. Extracted by percolation method using 96% ethanol and concentrated by rotary evaporator, then fractionated with n-hexane and concentrated. Formulation and evaluation of creams with doses of n-hexane 2.5, 5 and 10% fractions were made. The method of measuring anti-inflammatory used in this study refers to the method of inflammation-associated edema. Results: Evaluation of cream preparations F1, F2 and F3 stable during storage up to 12 weeks from organoleptic, homogeneity, pH (5.9-6.3), spreadability (2.42-2.80 cm2), good dispersibility and irritation test. The F2 formula is the best in terms of pH and cream spreadability tests. The comparative significance value of the anti-inflammatory activity test at F2 compared to hydrocortisone gel was not a significant difference (P> 0.05). Conclusion: Cream formulation F3 of the 5% dose of Rhaphidophora pinnata leaf hexane n fraction in the cream preparation has the same effectiveness as the comparison of hydrocortisone cream in the form of cream.